Colonial Educational Policy & Muhammadiyah’s Education (Analitical History Muhammadiyah in Yogyakarta 1912-1942) - Yahdan Ibnu Human Saleh (Al-Jami'ah: Journal of Islamic Studies, 1991)
This research takes object of Muhammadiyah Educational Development on the Islamic Village in Yogyakarta 1912-1942. Muhammadiyah was an Islamic Missionary Organization and movement founded on November 18, 1912 by kyai Haji Ahmad Dahlan at Yogyakarta. It had aim to spread of the true and genuine teaching of Islam among the population and especially among its members. If the various kinds of an economic, Social, Political, as well as cultural aspects were the whole process of growth of Indonesian Nationalism, Muhammadiyah, for the reason, could be said had the goal or value orientation. Because it could be considered as the Muslim, Social, educational and religious movement possessed the goal to attain away of life free from colonialism. In a colonialism situation nationalism might be seen as a social and moral force which had and orientation to wards the future. In the main while, Muhammadiyah might be understood as a group action or collective activity to face a condition of backwardness by responding according to its position. This organization fashioned nationalism by constituting and influential moral force, that tried to moralize all developments in the society, without any political ambition whatever, as a response to political, cultural and social conditions. Some social changes introduced in 1912-1942 with a formal and non-formal education system were adopted of the methods of the west, which were practiced in other activities. For these purpose, under the first four period charismatic had been set up and dedicated for the people’s welfare and progress. The social contribution given by Muhammadiyah in the field of social welfare from (1912-1942) were: bureaucratization as the process of rationalizing organization, the establishment of the new system of educational institution (1912, 1920, 1921, 1926, 1934, 1937), form of scout movement hizb al-wathan (1918), to educate young generation, the founding of hospital and clinic (1923) and orphanage (1925) among the Indonesian in general, and Muslim in particular, which were not only in backwardness, but also in weakest condition socially, economically and politically, suppressed by Duch colonialism. Muhammadiyah emphasized the importance of schools as means of education in both general and religious subjects. The combination of the two kinds of education so that became typical in all Muhammadiyah schools, from kindergartens to senior high schools. The school established by Muhammadiyah had been most beneficial to the Indonesian people, particularly in the Dutch Colonial rule when schools were rare. Colonial educational policy was only to supply skilled and semi-skilled laborers for industries and plantation owned by the Dutch and to fill jobs and lower government officials. It was not possible the Dutch policy to emancipate the Indonesian people from the backwardness and therefor the number of public school was kept as low as possible.